Polyoxometalate–Ionic Liquid-Catalyzed Ritter Reaction for Efficient Synthesis of Amides - Zhang, Lei; Chen, Bo; He, Peipei; Li, Guosong; Zhang, Lan-Cui; Gao, Shuang (Synlett, 2022)
A series of polyoxometalate-ionic liquid catalysts that combine the features of a polyoxometalate and an ionic liquid, with the introduction of acidity and miscibility, have been developed to promote the Ritter reaction. Among them, [BSmim]CuPW12O40 [BSmim = 1-methyl-3-(4-sulfobutyl)-1H-imidazol-3-ium] displayed the highest activity for the amidation of a variety of alcohols with nitriles, delivering the corresponding amide products in good to excellent yields. Furthermore, the reaction can be easily scaled up to a gram scale without losing eﬃciency. This process therefore provides an appealing way to prepare amides by a Ritter reaction using a polyoxometalate–ionic liquid-based catalyst.
Keywords: alcohols; nitriles; amides; ionic liquids; Ritter reaction; organocatalysis